Matematyka

Autorzy:Adam Makowski, Tomasz Masłowski, Anna Toruńska

Wydawnictwo:WSiP

Rok wydania:2015

Wykonaj działania 4.1 gwiazdek na podstawie 10 opinii
  1. Gimnazjum
  2. 1 Klasa
  3. Matematyka

`a)\ (3a+b)(b-2a)=3a(b-2a)+b(b-2a)=` 

`\ \ \ =ul(3ab)-6a^2+b^2-ul(2ab)=-6a^2+ab+b^2` 

 

`b)\ (2a-3)(3-a)-(2+a)(2a-1)=` 

`\ \ \ =2a(3-a)-3(3-a)-(2(2a-1)+a(2a-1))=` 

`\ \ \ =6a-2a^2-9+3a-(4a-2+2a^2-a)=` 

`\ \ \ =-2a^2+9a-9-(2a^2+3a-2)=` 

`\ \ \ =ul(-2a^2)+ul(ul(9a))-ul(ul(ul(9)))-ul(2a^2)-ul(ul(3a))+ul(ul(ul(2)))=`  

`\ \ \ =-4a^2+6a-7` 

 

`c)\ 2(a+3)(2a-5)-3(2-a)(2a+1)=(2a+6)(2a-5)-(6-3a)(2a+1)=` 

`\ \ \ =2a(2a-5)+6(2a-5)-(6(2a+1)-3a(2a+1))=` 

`\ \ \ =4a^2-10a+12a-30-(12a+6-6a^2-3a)=` 

`\ \ \ =4a^2+2a-30-(-6a^2+9a+6)=` 

`\ \ \ =ul(4a^2)+ul(ul(2a))-ul(ul(ul(30)))+ul(6a^2)-ul(ul(9a))-ul(ul(ul6))=`  

`\ \ \ =10a^2-7a-36` 

 

`d)\ (3+2a)(a^2+2a-3)=3(a^2+2a-3)+2a(a^2+2a-3)=` 

`\ \ \ =ul(3a^2)+ul(ul(6a))-9+2a^3+ul(4a^2)-ul(ul(6a))=` 

`\ \ \ =2a^3+7a^2-9`